Chronic Inactivation of the Orbitofrontal Cortex Increases Anxiety-Like Behavior and Impulsive Aggression, but Decreases Depression-Like Behavior in Rats - Kuniishi, Hiroshi; Ichisaka, Satoshi; Matsuda, Sae; Futora, Eri; Harada, Riho; Hata, Yoshio (Frontiers in Behavioral Neuroscience, 2017)
The orbitofrontal cortex (OFC) is involved in emotional processing, and orbitofrontal abnormalities have often been observed in various affective disorders. Thus, chronic dysfunction of the OFC may cause symptoms of affective disorders, such as anxiety, depression and impulsivity. Previous studies have investigated the effect of orbitofrontal dysfunction on anxiety-like behavior and impulsive aggression in rodents, but the results are inconsistent possibly reflecting different methods of OFC inactivation. These studies used either a lesion of the OFC, which may affect other brain regions, or a transient inactivation of the OFC, whose effect may be restored in time and not reflect effects of chronic OFC dysfunction. In addition, there has been no study on the effect of orbitofrontal inactivation on depression-like behavior in rodents. Therefore, the present study examined whether chronic inactivation of the OFC by continuous infusion of a GABAA receptor agonist, muscimol, causes behavioral abnormalities in rats. Muscimol infusion inactivated the ventral and lateral part of the OFC. Following a week of OFC inactivation, the animals showed an increase in anxiety-like behavior in the open field test and light-dark test. Impulsive aggression was also augmented in the chronically OFC-inactivated animals because they showed increased frequency of fighting behavior induced by electric foot shock. On the other hand, chronic OFC inactivation reduced depression-like behavior as evaluated by the forced swim test. Additionally, it did not cause a significant change in corticosterone secretion in response to restraint stress. These data suggest that orbitofrontal neural activity is involved in the regulation of anxiety- and depression-like behaviors and impulsive aggression in rodents.